2018
DOI: 10.1016/j.neuron.2018.04.025
|View full text |Cite
|
Sign up to set email alerts
|

Gamma Oscillation Dysfunction in mPFC Leads to Social Deficits in Neuroligin 3 R451C Knockin Mice

Abstract: In the original publication of this article, the sentence in the Introduction, ''In addition, reduced gamma oscillations and sharp-wave ripples in the hippocampus are associated with decreased extinction of contextual fear memory in the NL3 R451C KI mouse (Polepalli et al., 2017),'' the term ''NL3 R451C KI mouse'' should be ''NL3 fl /PV-cre mouse.'' This has now been corrected in the article online.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 0 publications
3
39
0
Order By: Relevance
“…Therefore, Irsp53 expression in glutamatergic neurons in the cortex, where Emx1 is strongly expressed, seems to be important for normal social interaction and locomotor activity. This is in line with the well-known importance of the PFC in the regulation of social cognition and interaction, previously reported in studies with human subjects as well as WT and mutant mice carrying ASD-and schizophrenia-related gene mutations (Ernst et al, 1997;Mundy, 2003;Pierce et al, 2004;Carper and Courchesne, 2005;Amodio and Frith, 2006;Gilbert et al, 2008;Rinaldi et al, 2008;Shalom, 2009;Courchesne et al, 2011;Yizhar et al, 2011;Testa-Silva et al, 2012;Liang et al, 2015;Barak and Feng, 2016;Ko, 2017;Selimbeyoglu et al, 2017;Cao et al, 2018;Pirone et al, 2018;Wang et al, 2018Wang et al, , 2019Guo et al, 2019;Lazaro et al, 2019;Phillips et al, 2019;Yoo et al, 2019). .…”
Section: Discussionsupporting
confidence: 88%
“…Therefore, Irsp53 expression in glutamatergic neurons in the cortex, where Emx1 is strongly expressed, seems to be important for normal social interaction and locomotor activity. This is in line with the well-known importance of the PFC in the regulation of social cognition and interaction, previously reported in studies with human subjects as well as WT and mutant mice carrying ASD-and schizophrenia-related gene mutations (Ernst et al, 1997;Mundy, 2003;Pierce et al, 2004;Carper and Courchesne, 2005;Amodio and Frith, 2006;Gilbert et al, 2008;Rinaldi et al, 2008;Shalom, 2009;Courchesne et al, 2011;Yizhar et al, 2011;Testa-Silva et al, 2012;Liang et al, 2015;Barak and Feng, 2016;Ko, 2017;Selimbeyoglu et al, 2017;Cao et al, 2018;Pirone et al, 2018;Wang et al, 2018Wang et al, , 2019Guo et al, 2019;Lazaro et al, 2019;Phillips et al, 2019;Yoo et al, 2019). .…”
Section: Discussionsupporting
confidence: 88%
“…Specifically, DEG and GSEA analyses identified genes or gene sets that have been strongly associated with ASD, including high-risk ASD genes (Abrahams et al, 2013), genes involved in brain development (Brambilla et al, 2003; Courchesne et al, 2007; Walsh et al, 2008; Hazlett et al, 2017), and genes associated with neuronal synapses (Zoghbi, 2003; Garber, 2007; Südhof, 2008; Bourgeron, 2009; Spooren et al, 2012; Jiang and Ehlers, 2013; Won et al, 2013; Ebrahimi-Fakhari and Sahin, 2015; Monteiro and Feng, 2017) and astrocytes (Clarke and Barres, 2013; Petrelli et al, 2016). In addition, our study demonstrated that Pv interneurons, which have been strongly implicated in ASD (Lawrence et al, 2010; Yizhar et al, 2011; Saunders et al, 2013; Barnes et al, 2015; Filice et al, 2016; Selimbeyoglu et al, 2017; Cao et al, 2018; Hashemi et al, 2018; Lee et al, 2018), exhibit an altered density in Tbr1 +/K228E mice. Moreover, the increased inhibitory synaptic transmission in layer 6 pyramidal neurons supports the role of an E/I imbalance in ASD (Rubenstein and Merzenich, 2003; Pizzarelli and Cherubini, 2011; Nelson and Valakh, 2015; Lee et al, 2017).…”
Section: Discussionsupporting
confidence: 52%
“…In addition, Cntnap2 -knockout mice, a mouse model of ASD (Peñagarikano et al, 2011), display pyramidal neuronal hyperactivity and social deficits that are normalized by stimulation of Pv interneurons (Selimbeyoglu et al, 2017). Moreover, mice harboring a neuroligin 3-R351C mutation, another mouse model of ASD (Tabuchi et al, 2007), display abnormal gamma oscillations involving Pv interneuronal hypo-excitability and behavioral deficits that are normalized by Pv interneuronal stimulation at a gamma frequency (40 Hz) nested at a theta frequency (8 Hz; Cao et al, 2018). Although these studies largely implicate decreased functions of Pv interneurons in the regulation of local brain oscillation and social interaction, the converse situation involving increased Pv neuronal density and output, as in our current study, might also induce functional abnormalities of Pv interneuron networks in the mPFC.…”
Section: Discussionmentioning
confidence: 99%
“…Animals have the tendency to seek novelty both in social and nonsocial stimuli to successfully respond to changing environments 44, 45 . Various animal models of ASD and schizophrenia have shown the defects in social recognition, social novelty preference, or social memory 7, 46, 47, 48 , which may reflect the problems in human patients with ASD or schizophrenia in expanding their social relationships.…”
Section: Discussionmentioning
confidence: 99%